1996
DOI: 10.3319/tao.1996.7.1.107(a)
|View full text |Cite
|
Sign up to set email alerts
|

Total Electron Content Obtained by Using the Global Positioning System

Abstract: A procedure is introduced to obtain the balance of measurements of differential group delays and differential carrier phase lead characteristics, both phenomena being due to the ionospheric total electron content (TEC) along the ray path from a Global Positioning System (GPS) satellite. It has been demonstrated that utilizing the measurement of both pseudorange and carrier phase recorded by genetic GPS receivers, the precision of the vertical TEC derived when the anti-spoofing (AS) is on can be as good as that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 3 publications
1
102
0
Order By: Relevance
“…(Sardon et al 1994;Leick 1995;Liu et al 1996). The slant total electron content, STEC, along ray path l between a GPS satellite, Tx, and a ground-based receiver, Rx, can be written as:…”
Section: Observations and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sardon et al 1994;Leick 1995;Liu et al 1996). The slant total electron content, STEC, along ray path l between a GPS satellite, Tx, and a ground-based receiver, Rx, can be written as:…”
Section: Observations and Analysesmentioning
confidence: 99%
“…To obtain a better estimate of earthquake hazard, a large amount and broad distribution of ground-based GPS receivers recording for longer periods of time are usually needed. While observing Earth's surface deformation, a network of GPS receivers can be employed to monitor the ionospheric total electron content (TEC) (Liu et al 1996). Liu et al (2001) analyzed the measurements of the Taiwan GPS network and reported significant decreases in the TEC on the 3rd and 4th days before the Chi-Chi earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Each satellite transmits two frequencies of signals, f 1 = 1575.42 and f 2 = 1227.60 MHz. Since the ionosphere is a dispersive medium, scientists are able to evaluate the ionospheric effects on the radiowave propagation or the corresponding ray path TEC with measurements of the modulations on carrier phases and code pseudoranges recorded by dual-frequency receivers (Sardón et al, 1994;Leick, 1995;Liu et al, 1996). Here, the slant TEC (STEC) between a GPS satellite and a ground-based receiver can be written as…”
Section: Observation and Simulationmentioning
confidence: 99%
“…• latitude by 1 • longitude, and 15 km altitude grid every 2 minutes. Meanwhile, based on Liu et al (1996), the TECs over 8 GPS stations are derived to monitor the ionospheric solar eclipse and storm signatures.…”
Section: Observation and Simulationmentioning
confidence: 99%
“…Owing to the use of two ultra high frequency (UHF, F1 ¼ 1575.42 MHz and F2 ¼ 1227.60 MHz) waves, the GPS studies are generally free from shortwave fadeout. Therefore, while performing the Earth's surface deformation observations, the same network of GPS receivers can also be used simultaneously and continuously to monitor the ionospheric TEC (Sardon et al 1994, Leick 1995, Liu et al 1996. Recently, an apparent reduction in GPS TEC was observed a few days prior to some strong earthquakes (Calais and Minster 1995, Liu et al 2001, Zhou et al 2009, Xia et al 2010.…”
Section: Introductionmentioning
confidence: 99%